Young readers in a Mandarin Chinese dual-language bilingual education programme. Issue 6 (3rd July 2022) - Sung, Ko-Yin
ABSTRACT: This study investigated the oral reading strategy use of 51 first-grade readers in a Chinese Dual-Language Bilingual Education (DLBE) programme. It attempted to answer the following research questions: (1) What reading strategies do first-grade Mandarin Chinese DLBE learners employ to decode Chinese text during oral reading? (2) Do the first-grade readers of different oral reading levels employ different strategies? Reading observations and prompts to the participants during and after reading were employed to capture the participants' strategy use. This study found that the participants most frequently used text editing strategies during oral reading. In addition, there were differences among readers of different reading levels. Efficient readers were better able to use a variety of strategies to facilitate reading, while less efficient readers often asked for help and blindly guessed the meanings and pronunciations of characters in the reading.